Difference between revisions of "009B Sample Midterm 1, Problem 4"
Jump to navigation
Jump to search
Line 7: | Line 7: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |'''1.''' Recall the trig identity | + | |'''1.''' Recall the trig identity |
|- | |- | ||
− | |'''2.''' How would you integrate <math style="vertical-align: -14px">\int \sin^2x\cos x~dx?</math> | + | | <math style="vertical-align: -2px">\sin^2x+\cos^2x=1</math> |
+ | |- | ||
+ | |'''2.''' How would you integrate <math style="vertical-align: -14px">\int \sin^2x\cos x~dx?</math> | ||
|- | |- | ||
| | | | ||
− | + | You can use <math style="vertical-align: 0px">u</math>-substitution. | |
+ | |- | ||
+ | | Let <math style="vertical-align: -2px">u=\sin x.</math> | ||
+ | |- | ||
+ | | Then, <math style="vertical-align: -1px">du=\cos x~dx.</math> | ||
+ | |- | ||
+ | | Thus, | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \sin^2x\cos x~dx} & = & \displaystyle{\int u^2~du}\\ | \displaystyle{\int \sin^2x\cos x~dx} & = & \displaystyle{\int u^2~du}\\ | ||
&&\\ | &&\\ | ||
& = & \displaystyle{\frac{u^3}{3}+C}\\ | & = & \displaystyle{\frac{u^3}{3}+C}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{\sin^3x}{3}+C.} | + | & = & \displaystyle{\frac{\sin^3x}{3}+C.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 30: | Line 39: | ||
|First, we write | |First, we write | ||
|- | |- | ||
− | | | + | | <math style="vertical-align: -13px">\int\sin^3x\cos^2x~dx=\int (\sin x) \sin^2x\cos^2x~dx.</math> |
− | + | |- | |
+ | |Using the identity <math style="vertical-align: -4px">\sin^2x+\cos^2x=1,</math> | ||
|- | |- | ||
− | | | + | |we get |
|- | |- | ||
− | | | + | | <math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math> |
− | |||
|- | |- | ||
|If we use this identity, we have | |If we use this identity, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int\sin^3x\cos^2x~dx} & = & \displaystyle{\int (\sin x) (1-\cos^2x)\cos^2x~dx}\\ | \displaystyle{\int\sin^3x\cos^2x~dx} & = & \displaystyle{\int (\sin x) (1-\cos^2x)\cos^2x~dx}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\int (\cos^2x-\cos^4x)\sin(x)~dx.} | + | & = & \displaystyle{\int (\cos^2x-\cos^4x)\sin(x)~dx.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
Line 51: | Line 60: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\cos(x).</math> Then, <math style="vertical-align: -5px">du=-\sin(x)dx.</math> | + | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: -5px">u=\cos(x).</math> | ||
+ | |- | ||
+ | |Then, <math style="vertical-align: -5px">du=-\sin(x)dx.</math> | ||
|- | |- | ||
− | | | + | |Therefore, |
− | + | |- | |
+ | | | ||
+ | <math>\begin{array}{rcl} | ||
\displaystyle{\int\sin^3x\cos^2x~dx} & = & \displaystyle{\int -(u^2-u^4)~du}\\ | \displaystyle{\int\sin^3x\cos^2x~dx} & = & \displaystyle{\int -(u^2-u^4)~du}\\ | ||
&&\\ | &&\\ | ||
& = & \displaystyle{\frac{-u^3}{3}+\frac{u^5}{5}+C}\\ | & = & \displaystyle{\frac{-u^3}{3}+\frac{u^5}{5}+C}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\frac{\cos^5x}{5}-\frac{\cos^3x}{3}+C.} | + | & = & \displaystyle{\frac{\cos^5x}{5}-\frac{\cos^3x}{3}+C.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | | <math>\frac{\cos^5x}{5}-\frac{\cos^3x}{3}+C</math> | + | | <math>\frac{\cos^5x}{5}-\frac{\cos^3x}{3}+C</math> |
|} | |} | ||
[[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']] |
Revision as of 11:01, 9 April 2017
Evaluate the integral:
Foundations: |
---|
1. Recall the trig identity |
2. How would you integrate |
You can use -substitution. |
Let |
Then, |
Thus, |
|
Solution:
Step 1: |
---|
First, we write |
Using the identity |
we get |
If we use this identity, we have |
|
Step 2: |
---|
Now, we use -substitution. |
Let |
Then, |
Therefore, |
|
Final Answer: |
---|